2011
DOI: 10.1007/s12098-010-0300-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Myeloid Leukemia in Children: Experience from a Tertiary Care Hematology Centre in India

Abstract: The present data suggests that 3 + 7 induction, followed by high dose cytarabine consolidation has low treatment related toxicity and resource utilization; however, relapse free survival is inferior to more intensive regimens, highlighting the need to intensify chemotherapy regimen once the treatment related mortality has been minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…TRM has been very high in our center, which indicates that we need to improve our supportive care. A very low TRM of 5.7% has been reported from another center in India in 35 patients of pediatric AML treated with less intensive protocol, but 48.5% relapsed [8].…”
Section: Pediatric Acute Myeloid Leukemia (Aml) Is the Final Frontiermentioning
confidence: 82%
“…TRM has been very high in our center, which indicates that we need to improve our supportive care. A very low TRM of 5.7% has been reported from another center in India in 35 patients of pediatric AML treated with less intensive protocol, but 48.5% relapsed [8].…”
Section: Pediatric Acute Myeloid Leukemia (Aml) Is the Final Frontiermentioning
confidence: 82%
“…ED rates varied from 3% to 59% (n=18 studies). ED rates were high overall, as only two studies reported ED rates below 5% [22,39]. In two studies [40,42], a drop in ED rate below 10% was achieved by optimization of supportive care measures.…”
Section: Treatment Outcomes Of Pediatric Aml In Lmicsmentioning
confidence: 94%
“…CR rates varied from 32% to 100% (n=19 studies), and nine studies described a CR rate of 80% or higher [22,27,28,30,36,39,40,42,45]. CR rates were over 64% in the remaining ten studies, with the exception of two which described CR rates of merely 35% [29,38].…”
Section: Treatment Outcomes Of Pediatric Aml In Lmicsmentioning
confidence: 99%
See 2 more Smart Citations